Observasi Home (Home Observation For Measurement Of The Environment Revisite) Sebagai Instrumen Pengukuran Lingkungan Rumah Dan Perkembangan Kognitif Anak Usia Dini - Tsurayya Syarif Zain (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
Cognitive development in pre-school age children is an important component that is important for developing children's thinking abilities and it is needed in the next stage of development. Several factors can determine the development of children's cognition, one of which is the home environment. Home is the environment that has the greatest influence on children's development. Totsika & Sylva (2004) designed HOME (Home Observation for Measurement of The Environment Revisited) as an environmental measurement with a systematic assessment of the environment that cares about children's development. The purpose of this instrument is to measure, in a natural context, the quality, and quantity of stimulation and support available to children in the home environment. This article aims to analyze research studies regarding HOME measurement as a predictor of cognitive development in pre-school children. The method used in this research is the literature review. The factors that are identified as components of the scale and the HOME score determine how well the child's cognitive development can be stimulated. HOME scores can also mediate the relationship between parental IQ and children's IQ and show that the genetic influence exerted on the family environment is closely related to children's cognitive development.